Airway epithelial cells enhance the immunogenicity of human myeloid dendritic cells under steady state. (22nd May 2017) - Agrawal, S.; Srivastava, R.; Rahmatpanah, F.; Madiraju, C.; BenMohamed, L.; Agrawal, A.
Summary: Dendritic cells (DCs) and airway epithelial cells (AECs) are in close proximity, and AECs secrete factors such as retinoic acid which induce tolerance in DCs at homeostasis. However, the question remains as to how DCs in the lung are able to respond to pathogens in the immunosuppressive environment. Using an in vitro human myeloid DC (mDC)‐AEC co‐culture system, we demonstrate that AECs induced several gene changes in the mDCs cultured with AECs compared to the mDCs not cultured with AECs. Analysis revealed that several chemokine genes were altered. These chemokine genes could serve to attract neutrophils, natural killer (NK) T as well as T helper type 1 (Th1)/Th2 cells to the airways. Genes priming lipid and major histocompatibility complex (MHC) class II antigen presentation were also up‐regulated, along with certain anti‐microbial protein genes. In addition, the expression and function of pathogen‐sensing Toll‐like receptors (TLRs) as well as Nod‐like receptors (NLRs) and their downstream signalling molecules were up‐regulated in mDCs cultured with AECs. Moreover, murine mucosal DCs from the lung expressed significantly higher levels of TLRs and NLRs compared to peripheral DCs from the spleen. These results indicate that AECs prime mDCs to enhance their immunogenicity, which could be one of the mechanisms that compensates for the immunosuppressive mucosal environment. Abstract : The dendritic cells (DCs) in respiratory mucosa exist in a suppressed state to prevent response to harmless inhaled antigens. Co‐culture of DCs with human airway epithelial cells (AECs) induced the upregulation of chemokine, pathogen recognition receptors and antigen presenting genes and proteins in DCs at homeostasis. AECs thus prime DCs to enhance their immunogenicity as a compensatory mechanism to circumvent the immunosuppressive environment.